PWE-096 Epigenetic dna methylation modifications following chronic iron exposure to colonocytes in vitro. (17th June 2017) - Horniblow, RD; Lai, S; Beggs, A; Iqbal, TH; Tselepis, C
Abstract : Introduction: Iron is an essential nutrient. However, in animal models, excess unabsorbed dietary iron which can reside within the colon for hours to days, has been shown to exacerbate inflammatory bowel disease and intestinal cancer. However, to date it remains unclear whether these detrimental effects are mediated though epigenetic modifications. Thus, the aim of this study was to chronically expose colonocytes to iron and determine the impact on genome-wide methylation. Method: Caco-2 cells were co-cultured in the presence or absence of iron (10 mM), with or without a dietary iron chelator (Manucol LD, 0.1% (w/v)) for 30 days. After this time period, DNA was harvested and methylation signatures were examined using Illumina Infinium Methylation450K BeadChip analysing 4 85 512 methylation sites. Intensity IDAT files were processed using ChAMP, which was used for the pre-processing and normalisation with SWAN. Probes found with an adjusted p-value of >0.01 were classified as significant differentially methylated probes (DMPs). Protein expression changes were examined by Western blotting. Results: The most significant methylation changes were observed between iron treated cells and control untreated cells (total of 60.04% DMPs with padj >0.01); all DMPs were found to by hypomethylated. Pathway specific genes that were hypomethylated included PI3K/AKT (18 genes), MAPK (16 genes), and RAP1/RAS (28 genes). Within the MAPK pathway, epidermal growth factor receptor (EGFR) was found to be 23.5% hypomethylated in the iron treated group compared to control cells (β=10.27); this increase was translated in the protein expression of EGFR. Relatively fewer changes were observed between iron and iron with Manucol LD treatment groups (total of 6.65% DMPs with Padj >0.01). No changes in methylation were observed between alginate treatments compared to control non-treated cells (0% DMPs with Padj >0.01). Conclusion: These studies suggest that chronic exposure of colonocytes to iron results in marked hypomethylation and this may be a contributory factor in iron mediated intestinal disease. Manucol LD had no impact on DNA methylation throughout the treatment. The contribution of the methylation changes to cell phenotype is currently being examined. Disclosure of Interest: None Declared